Sharing A Driver's Context With A Caller Via Continuous Audio Cues To Increase Awareness About Driver State - Janssen, Christian P.; Iqbal, Shamsi; Ju, Y. C. (Journal of Experimental Psychology: Applied, 2014)
In an experiment using a driving simulator we investigated whether sharing information of a driver’s context with a remote caller via continuous audio cues can make callers more aware of the driving situation. Increased awareness could potentially help in making the conversation less distracting. Prior research has shown that although sharing context using video can create such beneficial effects, it also has some practical disadvantages. It is an open question whether other modalities might also provide sufficient context for a caller. In particular, the effects of sharing audio, a cheaper, more salient, and perhaps more practical alternative than video, are not well understood. We investigated sharing context using direct cues in the form of realistic driving sounds (e.g., car honks, sirens) and indirect cues in the form of elevated heartbeats. Sound sharing affected the caller’s perception of the driver’s busyness. However, this had at most a modest effect on conversation and driving performance. An implication of these results is that although sharing sounds can increase a caller’s awareness of changes in the driver’s busyness, they need more training or information on how to leverage such context information to reduce disruption to driving. Limitations and implications are discussed.